Visceral Artery Aneurysms and Pseudoaneurysms: Etiology, Diagnosis, and Endovascular Management - Ju, Connie; Kapoor, Baljendra; Karuppasamy, Karunakaravel (Digestive Disease Interventions, 2018)
Visceral artery aneurysms (VAAs) are rare entities arising from several locations in the mesenteric vasculature. The etiology, clinical presentation, and subsequent management of these aneurysms vary widely. Although true aneurysms and pseudoaneurysms can present similarly on imaging, by definition they are distinct in their structural composition and hence may require tailored interventional planning. Treatment conventionally involves open surgery, endovascular intervention or careful observation. Recently, endovascular approaches have shown increasing popularity given the higher success rates and shorter lengths of stay with these procedures versus surgery. Optimal endovascular treatment planning is determined by the interventionalist based on unique features of each aneurysm and underlying vascular anatomy. This article reviews the etiology, diagnosis, and endovascular management for VAAs and pseudoaneurysms.
Keywords: visceral artery aneurysm; endovascular; treatment